Study on radial oil spray cooling of end windings with hairpin motors - JinCheng Feng; Ping Sun; Dong Wei; WeiBo Shi; Song Yang; Zhe Zhao (Case Studies in Thermal Engineering)
Hairpin motors were widely regarded for high slot fill rate, low DC resistance short, and end length compared to round-wire motors. Radial oil spray cooling can be implemented by opening holes in the motor casing or setting oil rings. Also, this cooling method can take away surface heat from the end windings of the motor by directly cooling them, effectively improving the motor power density. However, the radial oil spray cooling for hairpin motors end winding was less studied. This paper investigated the radial oil spray cooling characteristics of different numbers and types of nozzles under different flow rates. The results showed that cooling performance increased with increasing flow rates. The cooling uniformity increased with the increasing number of nozzles, but the increase in cooling uniformity decreased when the nozzles arrangement angle exceeded 180°. Full cone and fan nozzles both had a better cooling effect than column nozzles. When the nozzle spraying angle was smaller than the nozzle arrangement spacing angle, the greater the nozzle spraying angle, the better the overall cooling effect. Conversely, the larger the nozzle spraying angle, the worse the overall cooling effect. This study can help engineers implement radial oil spray cooling designs for hairpin motors.